Psychological Problems of Athletes in Undergoing Independent Training Programs During the Pandemic Covid-19 - Jatmiko Tutur; Suryanto; Priambodo Anung (Britain International for Academic Research (BIAR) Publisher, 2021)
The global pandemic caused by the Covid-19 virus reduces human activities in various aspects of life, including sporting events. Restrictions on activities on a large scale make sporting events that have the potential to gather large numbers of people prohibited from being held to prevent the transmission and spread of this virus. In addition to sporting events, preparatory exercises for sporting events must also be carried out independently in their respective homes. The implementation of independent training in the long term with supervision through online media has an influence on athletes in physical, technical, tactical and psychological performance. The purposes of this study are (1) to describe the psychological problems of athletes carrying out independent training programs during the covid-19 pandemic, (2) to explore the causes of psychological problems, (3) to explore the strategies chosen by athletes in overcoming psychological problems. The method used in this research is descriptive qualitative with a case study approach through in-depth closed interviews with sports athletes who run an independent training program during covid 19. Data analysis was carried out using the step of grouping problematic data that occurred and presented in the form of percentages and discussion The results of this study show Independent exercise programs at home have a psychological impact on athletes in the form of anxiety, boredom, stress, and obsession. Suggestions from the results of this study should be exercise in quarantine involving athletes and coaches in one camp equipped with training facilities and a recreational situation.